Delivery of goods to carriers in international sales: an examination of what It purported to be in Nigeria (2018)
This article deals with international sales. Specifically, it discusses the question of delivery of goods to the carrier and its implication that it shall be ‘prima facie deemed to be a delivery of the goods to the buyer’. The legal consequences in Nigeria of a contract entered into by parties of different origin with respect to delivery of goods to the carrier are examined. It further discusses how a breach of duties and obligations on the part of the parties can lead to the application of statutory exceptions. It notes that there are two international conventions ratified and domesticated in Nigeria, but one protects the interests of one party more than the other and the other also does the same with the interests of the other party. It considers the application of these international conventions on the issue of delivery of goods to the carrier. Furthermore, it also considers the application of Incoterms in Nigeria to carriage of goods and argues that the controversy generated in the United Kingdom by Vaughan Williams LJ and Buckley LJ, on the one hand, and Hamilton LJ, on the other hand, has reverberated to Nigeria. It points out a misconception in the application of law on this issue which has been accepted as a settled principle of law in Nigeria.